Penerapan Akad Murabahah Pada Pembiayaan Kpr Syariah Berdasarkan Fatwa Dsn Mui Pada Bank Syariah Indonesia Cabang Jelutung - Sofyan Nurcahyono; Habriyanto; Mohammad Orinaldi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
The author raises the title "Application of Murabahah Contracts in Syariah Mortgage Financing Based on the DSN-MUI FATWA at the Indonesian Syariah BANK Jelutung Branch". This study aims to provide input to BSI Jelutung Branch to pay more attention to the application of its Murabahah Agreement so that it does not come out of the FATWA DSN-MUI 04/DSN-MUI/IV/2000 concerning Murabahah. The formulation of the problem discussed in this thesis is: How is the implementation of the murabaha contract at the BSI Jelutung Branch? Is the implementation of the murabaha contract at the BSI Jelutung Branch in accordance with the DSN-MUI Fatwa? and what are the obstacles in implementing the DSN-MUI fatwa in Islamic banking activities? The author uses a qualitative data collection method, namely a method by conducting field surveys directly with existing sources. The author also uses other data collection techniques, namely interviews, namely the technique of conducting direct questions and answers to the authorities and the companies studied, in order to be able to complete more accurate data and information. The results of the study show that in general the implementation of the Murabaha contract at the BSI Jelutung Branch is in accordance with the DSN-MUI Fatwa. However, there are still provisions that are not in accordance with the provisions of the DSN-MUI Fatwa, namely incompatibility with Syariah KPR financing products, namely the price comparison is greater than conventional banks in Syariah KPR financing, where BSI Jelutung Branch should be able to provide more affordable prices to the public. especially Muslims.